PERBANDINGAN RISIKO INKONTINENSIA URIN TIPE STRESS ANTARA PERSALINAN NORMAL DAN SECTIO CAESAREA DI POPULASI WANITA INDONESIA: SYSTEMATIC REVIEW DAN META-ANALISIS - Suryoadji, Kemal Akbar; As’syifa, Salsa Billa; Surya Putra, Abdul Hafiidh; Kusuma, Fitriyadi (Khazanah: Jurnal Mahasiswa, 2024)
ABSTRACT Introduction: Stress urinary incontinence (SUI) is a common consequence of childbirth and pelvic floor dysfunction. The risk of SUI differs between vaginal delivery and cesarean section, but this comparison in the Indonesian female population remains unclear. Methods: This study is a systematic review and meta-analysis comparing the risk of SUI between vaginal delivery and cesarean section among Indonesian women using review manager 5.4. application. Literature searches were conducted in PubMed, Scopus, and Cochrane databases using relevant keywords. Results: Analysis of two studies involving 438 women revealed a lower risk of SUI in the cesarean section group (16 out of 233 women) compared to vaginal delivery (38 out of 205 women). The combined risk ratio was 0.41 (95% CI: 0.22–0.75), indicating that cesarean section significantly reduces the risk of SUI compared to vaginal delivery. Conclusion: Cesarean section is associated with a lower risk of SUI compared to vaginal delivery in the Indonesian female population. These findings may assist clinicians and patients in making informed decisions about childbirth methods.